Production status of Marwari goat in arid zone - B.K. Mathur and N.V. Patil, A.K. Patel, P.P. Rohilla (Indian Journal of Animal Production and Management, 2019)
Marwari goats are mainly distributed in seven districts of arid western Rajasthan. This goat is a mediumsized and uniformly black coloured animal with shiny light-gray skin. Horns are corkscrew type and animalshave a curly tuft of hair on forehead. The data on body weight and milk yield pertaining to 133 goats wereanalysed. The average body weights at birth, 3, 6, 9, 12, 15, 18, 21 and 24 months age were observed tobe 2.24, 8.79, 13.02, 15.76, 18.50, 22.0, 25.1, 26.0 and 28.20 kg respectively. Male animals attained higherbody weights than females and twin born animals gained lower body weight than single born till one year ofage; thereafter the body weight was more or less similar in both single and twin born kids. On an average23.3 percent twinning was observed in Marwari goats. Marwari goats kidded first time at the average ageof 25.5 months and most of the goats (64%) kidded in between age group of 18 to 27 months. Femaleborn with twin birth matured faster and kidded at about 2 years of age. The body weight at first kidding ofMarwari goats was more or less similar in both the categories. Twenty one percent Marwari goats wereobserved to be elite in the institute’s flock. Elite goats yielded 47% more milk (in 150-d lactation yield)over flock average. Goats with twin birth had significantly (P